A remark on Philos-type oscillation criteria for differential equations - Sugie Jitsuro (2020)
The purpose of this short note is to call attention to expressions of Philostype criteria for the oscillation of solutions of a simple differential equation. A perfect square expression is used to obtain an evaluation that plays an essential role in the proof of Philos-type oscillation theorems. The required condition is pointed out when using the perfect square expression. To simplify the discussion, here we deal with two second-order linear differential equations, but its content is also applied to a variety of equations.